“Mais, le lendemain matin”. Residues of the Ephemeral in Eighteenth-Century French Art - Ledbury, Mark (Status Quaestionis, 2025)
This essay discusses how the Ephemeral was understood in eighteenth-century France, and asks how we can track what remains of ephemeral community and artistic experiences. With the help of some very suggestive remarks on ephemeral experience by historian Arlette Farge, the essay explores various ways the intensity and togetherness of ephemeral experience leaves its mark on visual art, by traces and various forms of accretion visible in artworks themselves. The essay draws on the work of Gabriel de Saint Aubin, Jean-Honoré Fragonard and Jacques-Louis David.